Mevalonate kinase-deficient THP-1 cells show a disease-characteristic pro-inflammatory phenotype - Politiek, Frouwkje A.; Turkenburg, Marjolein; Ofman, Rob; Waterham, Hans R. (Frontiers in Immunology, 2024)
Bi-allelic pathogenic variants in the MVK gene, which encodes mevalonate kinase (MK), an essential enzyme in isoprenoid biosynthesis, cause the autoinflammatory metabolic disorder mevalonate kinase deficiency (MKD). We generated and characterized MK-deficient monocytic THP-1 cells to identify molecular and cellular mechanisms that contribute to the pro-inflammatory phenotype of MKD.Using CRISPR/Cas9 genome editing, we generated THP-1 cells with different MK deficiencies mimicking the severe (MKD-MA) and mild end (MKD-HIDS) of the MKD disease spectrum. Following confirmation of previously established disease-specific biochemical hallmarks, we studied the consequences of the different MK-deficiencies on LPS-stimulated cytokine release, glycolysis versus oxidative phosphorylation rates, cellular chemotaxis and protein kinase activity.Similar to MKD patients' cells, MK-deficiency in the THP-1 cells caused a pro-inflammatory phenotype with a severity correlating with the residual MK protein levels. In the MKD-MA THP-1 cells, MK protein levels were barely detectable, which affected protein prenylation and was accompanied by a profound pro-inflammatory phenotype. This included a markedly increased LPS-stimulated release of pro-inflammatory cytokines and a metabolic switch from oxidative phosphorylation towards glycolysis. We also observed increased activity of protein kinases that are involved in cell migration and proliferation, and in innate and adaptive immune responses. The MKD-HIDS THP-1 cells had approximately 20% residual MK activity and showed a milder phenotype, which manifested mainly upon LPS stimulation or exposure to elevated temperatures. Conclusion MK-deficient THP-1 cells show the biochemical and pro-inflammatory phenotype of MKD and are a good model to study underlying disease mechanisms and therapeutic options of this autoinflammatory disorder.